Interpretation of Double Taxation Conventions – The Judgement of the German Federal Fiscal Court (Bundesfinanzhof) in the Light Designer Case - Lang, Michael (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
In its judgement of 11 July 2018, I R 44/16, the German Bundesfinanzhof had to qualify income from a German resident arising from his activities as light designer in three different countries according to the respective DTCs. This gave the court the opportunity to consider the framework for solving qualification conflicts, in particular the view that Art. 23A Para. 1 OECD MC binds the state of residence to the assessment of the source state (Qualifikationsverkettung). This was, in conformity with its earlier jurisprudence, rejected by the court. However, this approach was included in the OECD Commentary in the year 2000. The court therefore also discussed the effect of the updated Commentary on treaties concluded before and after its adoption respectively. It held that this change to the Commentary has definitely no effect on treaties concluded before 2000. The court could leave it open whether the position articulated in the updated Commentary might have effects on the interpretation of new treaties. This contribution will examine this judgement in detail, providing an analysis of qualification conflicts and a critical appraisal of the court’s solution.